Construction of a cost management model in an underground mine - Escudero Simon, William (2022)
Mining activities are associated with the influence of external and internal factors. Companies have no control over external factors, such as the supply and demand of metals; however, internal factors, such as the optimization and management of their processes, are the responsibility of their managers and supervisors. Costs are the result of continuous improvement, process management, occupational safety management, environmental care, and social relations. In this context, it is necessary to have an adequate cost model. This research aims to show the construction of a new model for cost management in an underground mine that facilitates monitoring, control, and decision making in daily operations, called "MOGECOMS". One of the reports generated from the model is by 'cost center'. It presents the budget for December, the execution for December and the deviation for December, where the deviation is the sum of the technical deviation plus the economic deviation for December; it also presents the budget accumulated to December, executed accumulated to December and deviation accumulated to December, where the accumulated deviation is the sum of the technical deviation plus the economic deviation. In addition, the cost management model allows to generate costs reports by mineralized structures (vein, manto, body), by mining methods (cut and fill, sublevel stoping), by nature of expenditure, as well as fixed costs and variable costs, and determining the KPIs of the operations. By analyzing these reports, the model allows decision making and management of mine operations, thus making mining operations sustainable over time.